Renal Agenesis, Extramural Ectopic Ureter, and Nonfunctioning Urinary Bladder: A Difficult Clinical Case with an Innovative Approach - Armands Vekšins; Laura Voiko; Charlotte Sandersen; Ilze Dūzena; Olga Rabočaja (Case Reports in Veterinary Medicine)
Summary. A 7-month-old female Jack Russell Terrier weighing 4.6 kg was referred to a veterinary hospital for persistent urinary incontinence. Blood test results and vital signs were within the normal range. Computed tomography allowed the diagnosis of extramural ectopic ureter and unilateral renal agenesis. After the first neoureterocystostomy surgery, the dog had severe complications, such as hydroureter and hydronephrosis, so a second surgery was performed. A commercial ureteral stent was not an option, and it was decided to fabricate a homemade stent to avoid euthanasia. The stent used was a soft, DEHP-free PVC tube with a lumen of 3×4.1 mm and a length of approximately 40 mm that connected the ureter to the urinary bladder. Two years after surgery, the dog is in good general condition, and the results of regularly performed blood and urine tests are within the normal range for dogs.